Effects of sludge retention time on membrane fouling and microbial community structure in a membrane bioreactor - Ahmed, Zubair; Cho, Jinwoo; Lim, Byung-Ran; Song, Kyung-Guen; Ahn, Kyu-Hong (ELSEVIER SCIENCE BV, 2007)
In this study, the effect of sludge retention time (SRT) on membrane bio-fouling was investigated in a membrane bioreactor (MBR) equipped with a sequential anoxic/anaerobic reactor. Specific cake resistance (alpha), trans-membrane pressure (TMP), mixed liquor suspended solids (MLSS), particle sizes, extracellular polymer substances bound in sludge (bound-EPS) and their correlations with membrane bio-fouling were studied at different SRTs. As SRT decreased to 20 days, the bound-EPS per unit of biomass increased, and consequently, the value of a increased, which resulted in the rise of TMP. However, the reduction of the bound-EPS content was relatively small as compared to a significant decrease in the value of alpha at longer SRTs (above 60 days). These observations suggest that colloidal particles significantly contribute to membrane bio-fouling. In addition, the diversity of the microbial community structure of activated sludge in the MBRs was observed using the respiratory quinone profile. The ubiquinone species containing UQ-8, belonging to the class beta-Proteobacteria type were the major constituents of the microbial community structure. The mole fraction of menaquinone MK-6, -7 and -8(H2) increased as SRT increased. Thus, the results of this study indicate that growth of microorganisms belonging to the delta- and epsilon-subclass of Proteobacteria as well as the members of the Cytophaga-Flavobacterium cluster increased at longer SRTs. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: WASTE-WATER TREATMENT; QUINONE PROFILE METHOD; ACTIVATED-SLUDGE; RESPIRATORY QUINONES; SP-NOV.; PERFORMANCE; FILTRATION; OPERATION; SEWAGE; SYSTEM